Continuum modeling and simulation of multiphase diffusion through a porous solid. (March 2015) - Zhao, Qiangsheng; Papadopoulos, Panayiotis
A theory is proposed for the continuum modeling of liquid and gas diffusion through a deformable porous solid. The solid and the voids are locally homogenized to yield a macroscopic solid phase. Liquid saturation of the voids and gas pressure are included as state variables to model diffusion. A model based on the proposed theory is implemented numerically using the finite element method, and tested with three simulations on sand and Nafion.